The New Comprehension of History During The Second Institutional Period of Ottoman Era: The Impact of Essai Sur L'histoire De L'islamisme of Dozy - YENİLMEZ, HASAN; ÜSTÜN, İSMAİL SAFA (KARABUK UNIV, 2016)
During the Second Constitutional Period of Ottoman era, the translation movement of positivist and materialist texts from the West affected a number of the Ottoman intellectuals. The effects of these ideological movements could clearly be seen in their works. Following these ideological changes, the Ottoman intellectual's perceptions towards classical Islamic history has been completely changed. Also, during the constitutional period, the Islamic history literature seems to be demonstrating a different sense of historical approach. It is also observed that during the second constitutional period along with the increased translation activities from the West, Ottoman intellectuals started to accommodate the scientific historiography approach. In his translation of Essai Sur L'histoire De L'islamisme, Abdullah Cevdet translated the title as History of Islam and he called Dozy a complete neutral and a product of reasoning. The majority of Ottoman intellectuals gravely criticized Cevdet's work at that time. This article describes the works which refuses the works of Cevdet and analyzes how they try to explain the concepts like Miracle and the Mirac which are difficult to describe with scientific method. In this context the works of Manastirli Ismail Hakki, Nevsehirli Hayreddin, Sehbenderzade Filibeli Ahmed Hilmi also examined.
Keywords: Abdullah Cevdet; Dozy; History of Islam; Manastirli Ismail Hakki; Sehbenderzade Filibeli Ahmed Hilmi; Nevsehirli Hayreddin; Miracle; Mirac